Issues in International Telecommunications Policy A Sourcebook - George Washington Univ., Washington, DC. Center for Telecommunications Studies; Yurow, Jane H.; George Washington Univ., Washington, DC. Center for Telecommunications Studies ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1983)
Designed to provide the legal practitioner with the basic tools to understand the international telecommunications field, this document was originally prepared in connection with the 1983 Conference on International Telecommunications. An introductory chapter focuses on where policy is made and lists international organizations involved with telecommunications policy; United States Government Executive Branch Agencies, their functions, and staff; and relevant congressional committees and their key members, staff, and current interest in international telecommunications. Other pertinent legislative branch organizations are also described. Separate chapters then cover the International Telecommunication Union, regulatory environment, transborder data flow, telecommunications and trade policy, and intellectual property. For each topic, an introductory essay describing important developments and major concerns is followed by selected materials which include United States laws, regulations, and proposed legislation; judicial and administrative decisions; treaties and agreements; a description of the ongoing activities of key international organizations; a description of the Executive Branch Interagency and Public Advisory Committees; a selected bibliography; and additional information. A glossary and conclusions are provided. (LMM)
Availability: George Washington University, Center for Telecommunications Studies, Washington, DC 20052 ($49.95 per copy + $2.00 postage and handling; ten or more, $35.00 per copy).
Microfiche.
Keywords: Annotated Bibliographies; Court Litigation; Federal Government; Federal Legislation; Federal Regulation; Foreign Countries; Government (Administrative Body); International Organizations; International Programs; Policy Formation; Telecommunications; Treaties; International Telecommunication Union; Guides, General; Reference Materials, Directories/Catalogs.